2021
DOI: 10.1016/j.scs.2021.103256
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control of high-rise building mechanical ventilation system for achieving low risk of COVID-19 transmission and ventilative cooling

Abstract: As suggested by many guidelines, a high ventilation rate is required to dilute the indoor virus particles and reduce the airborne transmission risk, i.e., dilution ventilation (DV). However, high ventilation rates may result in high energy costs. Ventilative cooling (VC), which requires high ventilation rates like DV, is an option to reduce the cooling energy consumption. By combining DV and VC, this paper investigated the operation of the mechanical ventilation system in high-rise buildings during the COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 38 publications
0
29
0
3
Order By: Relevance
“…By analysing the obtained results, starting from the no mask case, it is possible to notice that, for a ventilation rate equal to 18 vol/h (RS), an infection probability of 2.38% is achieved, which is above the 1% threshold value considered as a safe one, as also specified in literature [ 22 ]. By rising the ACH to 31 vol/h (PS2 and PS2.1), an infection probability reduction equal to ∼ 40% vs. RS is detected.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…By analysing the obtained results, starting from the no mask case, it is possible to notice that, for a ventilation rate equal to 18 vol/h (RS), an infection probability of 2.38% is achieved, which is above the 1% threshold value considered as a safe one, as also specified in literature [ 22 ]. By rising the ACH to 31 vol/h (PS2 and PS2.1), an infection probability reduction equal to ∼ 40% vs. RS is detected.…”
Section: Resultsmentioning
confidence: 98%
“…The role of mechanical ventilation is investigated also in Ref. [ 22 ] where the authors study a high rise institutional building located in Montreal. The analysis focuses on the assessment of the optimal outdoor airflow rate guaranteeing a Covid-19 contagion risk below 1% (assumed as a safe threshold), at the variation of quanta emission rate.…”
Section: Introductionmentioning
confidence: 99%
“…Higher ventilation is suggested to reduce the risk of airborne infection, also known as dilution ventilation ( Qian et al, 2020 ). However, high ventilation also increases energy consumption and operating cost Sha et al (2021) . suggested ventilative cooling and dilution ventilation that could reduce energy consumption in high-rise buildings and, thus, reduce the risk of virus transmission Henriques et al (2021) .…”
Section: Resultsmentioning
confidence: 99%
“…Several recent studies have explored the energy consumption of HVAC systems in different buildings when maintaining a low risk of COVID-19 transmission. For instance, Sha et al [ 43 ] investigated the relationship between increased ventilation rate and energy consumption in high-rise buildings, and found a ventilation rate of 5.2 ACH is required to maintain infection risk under 1% when conducting social distance and wearing masks for 8-h exposure, leading to energy consumption of 265 MWh for chiller system, and 252 MWh for fans. Wang et al [ 44 ] found that the standard minimum airflow rate is insufficient to maintain the infection risk at low level, and the energy consumption can reach up to 2.9 kWh for 1-h exposure when limiting the infection risk below 2%.…”
Section: Discussionmentioning
confidence: 99%